Sulphasalazine induced hepatitis in juvenile rheumatoid arthritis. Issue 2 (February 1992) - Caspi, D; Fuchs, D; Yaron, M
Abstract : Two 19 year old patients with juvenile chronic arthritis developed liver toxicity during treatment with sulphasalazine. A significant increase in the levels of liver enzymes in serum samples was noticed in relation to the initiation of treatment in one patient and to the increase in dose in the second. The enzymes returned to normal levels 14 days after the drug had been stopped. A rechallenge in one of the patients caused re-exacerbation. This is the first report of liver toxicity induced by sulphasalazine in juvenile chronic arthritis. As spontaneous liver involvement in juvenile chronic arthritis is not rare, the possibility of drug induced hepatitis should be recognised in these patients.